2019
DOI: 10.1111/bjh.15876
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative sensory testing in children with sickle cell disease: additional insights and future possibilities

Abstract: Summary Quantitative sensory testing (QST) is used in a variety of pain disorders to characterize pain and predict prognosis and response to specific therapies. In this study, we aimed to confirm results in the literature documenting altered QST thresholds in sickle cell disease (SCD) and assess the test–retest reliability of results over time. Fifty‐seven SCD and 60 control subjects aged 8–20 years underwent heat and cold detection and pain threshold testing using a Medoc TSAII. Participants were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
3
10
0
Order By: Relevance
“…The experimental pain sensitivity reported here was generally comparable to previously published data in children with SCD 13,32,39 . Due to a small sample size and missing follow‐up QST measurements post‐HCT, we were limited in the conclusions that can be drawn.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The experimental pain sensitivity reported here was generally comparable to previously published data in children with SCD 13,32,39 . Due to a small sample size and missing follow‐up QST measurements post‐HCT, we were limited in the conclusions that can be drawn.…”
Section: Discussionsupporting
confidence: 80%
“…40 Experimental pain sensitivity in SCD may also vary with age, 32 sex, 13 psychological factors, 13,41 pain frequency, 13 and may also change in response to interventions such as hydroxyurea. 39 Future studies should consider these confounding factors in studying…”
Section: "Being Active Again Just Knowing That I Get To Do Stuff That...mentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that females were more sensitive to all modalities at the thenar eminence and dorsolateral foot, and that older subjects less sensitive to all at those sites except HPT and PPT at the thenar eminence and PPT at the dorsolateral foot. Sex differences are not commonly seen in QST in SCD studies (17,18). However, Brandow et al (13) have reported that both older SCD subjects and older non-SCD controls were more sensitive to heat and mechanical stimuli and that although there were no overall significant sex differences between groups, females with SCD had higher mechanical pain thresholds compared to males.…”
Section: Discussionmentioning
confidence: 99%
“…In SCD, the thermal pain threshold (TPT) to cold <17.01°C and heat <43.91°C are indicative of impaired nerve sensitivity, and pressure pain threshold (PPT) <4.42 g is indicative of the existence of altered sensory function ( 68 ). Thermal pain threshold (TPT) assessment with temperature in 32°C baselines and an increasing/decreasing temperature at a rate of 1.5°C/s is used in clinical settings (ICC >0.55) ( 69 ). In cases of non-SCD pain, specifically osteoarthritis of the knee, the PPT increasing pressure at a rate of 0.5 kgf/s has a good diagnostic reliability value varying according to the evaluated joint site (ICC: 0.64–0.73) ( 70 ).…”
Section: Maladaptive Cns Plasticity Mechanisms and Ways To Evaluate Itmentioning
confidence: 99%